Accumulation and distribution of ions of heavy metals in cells of moss Drepanocladus aduncus (Hedw.) Warnst (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Accumulation of high level of heavy metals ions (Pb2+, Cu2+ and Cd2+) from 1,0-10,0 μМ solutions is revealed for the moss D. aduncus. The analysis of absorbed ions is shown that ~87% Pb2+, ~68% Cu2+ and ~96% Cd2+ are localized inside a cell, ~13% of lead ions, ~32% of copper ions and ~4% cadmium ions being kept by components of cell’ wall. It is possible that the difference in ions’ distribution in moss gametophyte cells is decisive in determining the toxicity of cadmium to be higher than that of lead and copper causing absence of their desorbtion as well. Usage of D. aduncus for elaborating biological methods of diagnostic and purification of polluted ecotopes is justified.
Keywords: heavy metals, accumulation, distribution in cells, Drepanocladus aduncus.